The greening of the Northern Great Plains and its biogeochemical precursors. (12th May 2020) - Brookshire, E. N. Jack; Stoy, Paul C.; Currey, Bryce; Finney, Bruce
Abstract: Vegetation greenness has increased across much of the global land surface over recent decades. This trend is projected to continue—particularly in northern latitudes—but future greening may be constrained by nutrient availability needed for plant carbon (C) assimilation in response to CO2 enrichment (eCO2 ). eCO2 impacts foliar chemistry and function, yet the relative strengths of these effects versus climate in driving patterns of vegetative greening remain uncertain. Here we combine satellite measurements of greening with a 135 year record of plant C and nitrogen (N) concentrations and stable isotope ratios (δ 13 C and δ 15 N) in the Northern Great Plains (NGP) of North America to examine N constraints on greening. We document significant greening over the past two decades with the highest proportional increases in net greening occurring in the dries and warmest areas. In contrast to the climate dependency of greening, we find spatially uniform increases in leaf‐level intercellular CO2 and intrinsic water use efficiency that track rising atmospheric CO2 . Despite large spatial variation in greening, we find sustained and climate‐independent declines in foliar N over the last century. Parallel declines in foliar δ 15 N and increases in C:N ratios point to diminished N availability as the likely cause. The simultaneous increase in greening and decline in foliar N across our study area points to increased N use efficiency (NUE) over the last two decades. However, our results suggest that plant NUE responses are likely insufficient to sustain observed greening trends in NGP grasslands in the future. Abstract : See also the Commentary on this article by Craine, 26, 5353–5355. We combine satellite measurements with a 135 year record of plant carbon (C) and nitrogen (N) concentrations and stable isotope ratios (δ 13 C and δ 15 N) in the Northern Great Plains (NGP) of North America to examine N constraints on vegetative greening. We document significant greening over the past two decades that was preceded by spatially uniform increases in leaf‐level intercellular CO2 and intrinsic water use efficiency, but sustained declines in foliar N and δ 15 N over the last century. Our results suggest that N may constrain future NGP vegetation responses to climate change and CO2 enrichment.